Intelligent Data Engineering and Automated Learning -- IDEAL 2012 13th International Conference, Natal, Brazil, August 29-31, 2012, Proceedings - Yin, Hujun; Costa, Jose A.F; Barreto, Guilherme (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2012)
This book constitutes the refereed proceedings of the 13th International Conference on Intelligent Data Engineering and Automated Learning, IDEAL 2012, held in Natal, Brazil, in August 2012. The 100 revised full papers presented were carefully reviewed and selected from more than 200 submissions for inclusion in the book and present the latest theoretical advances and real-world applications in computational intelligence.